Heteromagnetic Microelectronics Microsystems of Active Type - Ignatiev, Alexander A.; Lyashenko, Alexander V. (Springer New York : Imprint: Springer, 2010)
Heteromagnetic Microelectronics: Microsystems of Active Type, by Alexander A. Ignatiev of Saratov State University and Alexander V. Lyashenko of JSC Research Institute Tantal in Russia, offers a very detailed and specialized account of the author's research and development of heteromagnetic materials and devices. The book is based on original material from the author's programs of designing heteromagnetic microsystems. Polyvalent, multiple parameter magneto-semiconductor microsystems are described and the book reports on extensive experimental and theoretical results of research in a range of frequencies up to 1000 GHz. For the first time the direction of satisfying criteria, and burst technologies, which can make a subject of discovery, are discussed in great detail. This book is intended for post-graduate students and researchers specializing in the design and application of heteromagnetic materials and devices. Alexander A. Ignatiev is author of Magnetoelectronics of Microwaves and Extremely High Frequencies in Ferrite Films (Springer, 2009).